PARALLEL LINE IN TIMERIDERS BY ALEX SCARROW - Asia Susanti; Ansor Putra (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This research is intended to analyze the represented of parallel line in TimeRiders using theory of Brian McHale’s Postmodernist Fiction. The research question of this study is formulated: “how is parallel line represented in TimeRiders?”. The objective of this study is to describe parallel line which is represented in TimeRiders. The source of data in this study is TimeRiders novel by Alex Scarrow that is published in 2007. The data was collected through annotating, previewing, and interpreting to get complete analysis about Parallel Line in TimeRiders. Theory of Brian McHale’s Postmodernist Fiction is used as tool for analyzing the finding in the parallel line in TimeRiders. The result of analysis showed that parallel line is represented in TimeRiders, parallel line was represented though time travel. Parallel line connected science fiction and strategy postmodern in this novel. Parallel line caused the application of superimposition in TimeRiders. Superimposition occured in four dimension, they are superimposition in place, superimposition in character, superimposition in space, and superimposition in time. Time travel was done by some characters for several time during 2026, 2001, 1941, 1963, and 1956. The purpose of time travel by Liam is to correct the history that was changed by Kramer, and to correct history is the goal of postmodernism. The history was changed after Kramer fought with Hitler, and he lead Nazi. Kramer expanded his governer in New York. Time travel is one part of science fiction based on parallel line definition. That is why, TimeRiders has science fiction genre. TimeRiders with its science fiction has done alternative history, because of characteristic does not believe history, because history is made by people. Keywords: parallel line, time travel, science fiction, superimposition.